People with intellectual and mental disabilities in the social protection system in Serbia between community and institutionalization - Stankovic, Dragana; Brkic, Miroslav (Ревија за социјална политика/Journal of Social Policy, 2015)
The process of deinstitutionalization is one of the directions of the social protection system reform in Serbia that has started at the beginning of the year 2000 and as one of the reform’s priorities is incorporated in strategic documents and laws. In terms of human rights of persons with intellectual and mental disabilities, the institutions, but also society as a whole, show to a great extent insufficient focus and commitment. Compliance with the standards defined by the UN Convention on the Rights of Persons with Disabilities, ratified by Serbia what makes it legally binding document, has remained just at the level of the governmental formal commitment. Despite legislative changes aimed at protecting the rights of people with intellectual and mental disabilities, the number of those people in the residential institutions is still high. The key assumption of the deinstitutionalization process - development of community-based services, what should ensure getting the necessary support in the natural environment (and prevention of the institutional care as the same time), hasn’t kept the anticipated pace.